Meanings of the Gastronomic Culture of the Vilnius College Jesuit Community - Laužikas, Rimvydas (Senoji Lietuvos literatūra, 2020)
The object of the study presented in the article is the gastronomic culture of the Vilnius College Jesuit community in the seventeenth-eighteenth centuries. The aim of the study is to define the peculiarities of the gastronomic culture of the Vilnius College Jesuit community by analysing the information found in the sources about the main dishes and drinks during fasting and regular times, and to describe the relationship of this local gastronomic culture with formal rules and community-specific informal practices governing the life of the Jesuits. The study provides a comparison of the gastronomic culture of the said Jesuit community with the gastronomic cultures of the manors of the rulers and the nobles of the Grand Duchy of Lithuania, other religious orders in Lithuania, and Jesuits in other European countries.This study applies a theoretical approach based on the concept of the semiosphere of Yuri Lotman, the founder of the Tartu semiotic school, which allows formulating the hypothesis that the Society of Jesus with its internal regulation is an independent structure of the semiosphere, which, when established in a particular geographical area (in our case, in Vilnius, Lithuania), interacts with the culture of that place (the Grand Duchy of Lithuania) as a peculiar, separate, and independent structure of the semiosphere forming various creolized spaces.It was established during the study that the absolute majority of dishes mentioned in the lists of the Jesuits of Vilnius College were typical of the cuisine of the nobility of the Grand Duchy of Lithuania in the seventeenth-eighteenth centuries. It is also interesting that, as befits the dietary style of the Jesuits, these dishes form a kind of mixture of aristocratic and peasant cuisine: a peculiar gastronomic tradition with extraordinary ordinariness. Some dishes are not typical of the current territory of Lithuania and can be considered (again, in accordance with the dietary style of the Jesuits) a gastronomic adaptation to the eating habits of the people who arrived in Vilnius and joined the community.On the other hand, the gastronomic culture of the community demonstrates the striking elements of the monastic gastronomy characteristic of the Society of Jesus: a clear ecclesiastical calendar (fasting, celebrations); consumption of significantly larger amounts of fish compared to the cuisine of the nobles of the Grand Duchy of Lithuania; the pursuit of moderate alcohol consumption, and association of eating with spiritual exercises.Compared with the seventeenth-eighteenth-century gastronomic tradition of the Grand Duchy of Lithuania, the gastronomic tradition of Vilnius Jesuits is similar to the gastronomic culture of the upper class of the nobility and the nobles. This is clearly demonstrated by daily consumption of meat and its quantities, predominant types of ‘higher status’ meat (beef, veal, lamb, large birds, and songbirds), foodstuffs expensive for that time (white bread, eggs, sour cream, butter, rice, spices), a sufficiently wide range of vegetables, more luxurious drinks (mead, wine, bitters), and the use of imported spices for food seasoning.Compared to other Lithuanian convents (for instance, the Dominicans of Palėvenė), the food of Vilnius Jesuits was more European and urban. Compared to the Roman Jesuits, the food was heavier, meatier, and fatty; it contained smaller amounts of vegetables and more cereal dishes characteristic of the gastronomic tradition of the temperate climate zone.In summary, the study confirmed the hypothesis that gastronomy of the Vilnius Jesuit community is an excellent example of the creolized space of gastronomic cultures of the Vilnius College Jesuit community and the nobility of the Grand Duchy of Lithuania. In this case, the gastronomic semiosphere of the Jesuits operates on a more conceptual level as a set of ideas, rules, principles, symbols, while the tradition of the local nobility in the Grand Duchy of Lithuania operates on a more practical level as ingredients, recipes, and cooking technology.
Keywords: Society of Jesus; gastronomic culture; semiosphere; Vilnius; Grand Duchy of Lithuania